Minding the markets : an emotional finance view of financial instability - Tuckett, David (Houndmills : Palgrave MacMillan, 2011)
'In this groundbreaking book, Tuckett argues that most economists' explanations of the financial crisis miss its essence; they ignore critical components of human psychology. He offers a deeper understanding of financial market behavior and investment processes by recognising the role played by unconscious needs and fears in all investment activity'--
Includes bibliographical references (p. 213-221) and indexes.
Keywords: Investments -- Psychological aspects; Investments -- Decision making; Global Financial Crisis, 2008-2009